2017
DOI: 10.2967/jnumed.117.194373
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Heart-to-Mediastinum Ratio of 123I-MIBG Uptake Using Dual-Isotope (123I-MIBG/99mTc-Tetrofosmin) Multipinhole Cadmium-Zinc-Telluride SPECT in Patients with Heart Failure

Abstract: The aim of this retrospective study was to compare the heart-to-mediastinum ratio (HMR) of I-metaiodobenzylguanidine (I-MIBG) uptake obtained using a multipinhole cadmium-zinc-telluride (CZT) camera with that obtained using conventional planar imaging. Forty consecutive heart failure patients underwent planar acquisition 4 h afterI-MIBG injection (191 ± 41 [mean ± SD] MBq). To localize the heart using the CZT camera, Tc-tetrofosmin (358 ± 177 MBq) was administered and dual-isotope acquisition was performed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…However, there are only a small number of studies evaluating cardiac sympathetic innervation imaging with these new generation detectors [21][22][23] and only a few studies have compared H/M ratio determined using CZT acquisition versus that determined using A-SPECT [13,14]. Bellevre et al demonstrated that determination of the late H/M ratio of 123 I-MIBG uptake using a parallel-collimator CZT camera (D-SPECT, Spectrum Dynamics Medical, Caesarea, Israel) was feasible, reliable and equivalent to H/M ratio using A-SPECT in patients with heart failure [13].…”
Section: Global and Regional Sympathetic Cardiac Innervationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are only a small number of studies evaluating cardiac sympathetic innervation imaging with these new generation detectors [21][22][23] and only a few studies have compared H/M ratio determined using CZT acquisition versus that determined using A-SPECT [13,14]. Bellevre et al demonstrated that determination of the late H/M ratio of 123 I-MIBG uptake using a parallel-collimator CZT camera (D-SPECT, Spectrum Dynamics Medical, Caesarea, Israel) was feasible, reliable and equivalent to H/M ratio using A-SPECT in patients with heart failure [13].…”
Section: Global and Regional Sympathetic Cardiac Innervationmentioning
confidence: 99%
“…In contrast, Blaire et al using a multi-pinhole CZT camera (Discovery NM 530c, GE Healthcare) found almost perfect concordance between H/M ratio derived from transaxial SPECT images and H/M ratio from planar ones however concordance between H/M ratio from re-projected images and planar ones was only moderate. Blaire et al considered that was related to the multi-pinhole collimation, which is responsible for a truncation artifact that interferes with the mean counts of the myocardial ROI [14].…”
Section: Global and Regional Sympathetic Cardiac Innervationmentioning
confidence: 99%
“…4 However, the recent development of a calibration phantom-based standardization method provides optimal conversion coefficients for most of the Anger-type camera-collimator combinations. 5,6 The standardization method could be applied to cadmium-zinc-telluride (CZT) cameras, either by empirical conversion equation between two systems with a phantom study 7,8 or calibration phantom experiments as described for Anger cameras. 9 On the other hand, the assessment of regional 123 ImIBG uptake with SPECT has not been standardized so rigorously yet.…”
Section: I-mibg Myocardial Uptake Parametersmentioning
confidence: 99%
“…In the context of a new era for medical therapy of ATTR cardiac amyloidosis, there is a need for quantitative approaches that would be useful for diagnosis, assessment of patient prognosis, and also therapeutic response. With the widespread use of cadmium zinc telluride (CZT)-based single-photon emission computed tomography (SPECT) camera, it is now feasible to propose a semi quantitative assessment of a cardiac tracer uptake using either 3D reconstructed acquisition or reprojected planar images [16,17].…”
Section: Introductionmentioning
confidence: 99%